2009
DOI: 10.4049/jimmunol.0803767
|View full text |Cite
|
Sign up to set email alerts
|

The C-Type Lectin-Like Receptor CLEC-1, Expressed by Myeloid Cells and Endothelial Cells, Is Up-Regulated by Immunoregulatory Mediators and Moderates T Cell Activation

Abstract: C-type lectin receptors have recently been described as playing crucial roles in immunity and homeostasis since these proteins are able to recognize pathogens as well as self-Ags. We identified the C-type lectin-like receptor-1, CLEC-1, as being overexpressed in a model of rat allograft tolerance. We previously described in this model the expression of numerous cytoprotective molecules by graft endothelial cells and their interplay with regulatory CD4+CD25+ T cells. In this study, we demonstrate that CLEC-1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 37 publications
(53 reference statements)
7
60
0
Order By: Relevance
“…Almost all cultured moDCs express cell-surface CLEC-1, which is largely coexpressed with the other CLR DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN); however, in contrast to blood, CLEC-1 does not appear to be restricted to the CD16 2 subpopulation (Figure 1Ci-ii). Importantly, as we previously described in rats, 4 CLEC-1 expression is decreased on human moDCs by inflammatory stimuli such as toll-like receptor (TLR) ligands, and is upregulated by TGF-b (Figure 1Ciii-iv). By IHC, we confirmed that CLEC-1 expression is mostly intracellular for ECs, and at the cellsurface for moDCs and monocytes (Figure 1Di-ii).…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Almost all cultured moDCs express cell-surface CLEC-1, which is largely coexpressed with the other CLR DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN); however, in contrast to blood, CLEC-1 does not appear to be restricted to the CD16 2 subpopulation (Figure 1Ci-ii). Importantly, as we previously described in rats, 4 CLEC-1 expression is decreased on human moDCs by inflammatory stimuli such as toll-like receptor (TLR) ligands, and is upregulated by TGF-b (Figure 1Ciii-iv). By IHC, we confirmed that CLEC-1 expression is mostly intracellular for ECs, and at the cellsurface for moDCs and monocytes (Figure 1Di-ii).…”
Section: Resultsmentioning
confidence: 64%
“…4,5,8 qRT-PCR analysis in pooled organs demonstrates a strong expression of CLEC1A transcripts in placenta and lung, and a more moderate expression in the lymphoid organs including spleen, LNs, thymus, and tonsils (supplemental Figure 4i). In human cell subtypes, abundant CLEC1A transcripts were found in neutrophils, monocytes, moDCs, and HAECs (supplemental Figure 4ii).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, other lectin-like receptors may replace the function of Ly49 family proteins. In this regard, DECTIN-1 and CLEC-1, expressed in DCs, have been demonstrated to be involved in the fate determination of T cells between Tregs and Th17 cells (28)(29)(30). Lectin-like receptors seem to be more widely involved in the regulation of DC functions than was previously supposed.…”
Section: Figurementioning
confidence: 80%